Relation between General Health and Procrastination - M. golmohammadian; P. yaseminejad; Z. Feizabadi Farahani; N. Naderi (روانشناسی بالینی و شخصیت, 2013)
This research was conducted for recognizing the relation between procrastination and high school students’ general health. Statistical population of the study was all students of girl high schools in Western Islam Abad. 116 students were selected through random cluster sampling. Research tools included Schmitz, Deihel, and Schwarzer procrastination questionnaire, and general health (GHQ-28). Pearson correlation coefficient, step-by-step regression, and single-way variance analysis were applied for data analysis. Analysis results showed that there is positive meaningful relation between general health and procrastination. It means that the more procrastination and delay is among students, the more general health problems they have. This relation was higher for sub-scales such as anxiety and depression but no meaningful correlation between other sub-scales and procrastination. Step-by-step regression results indicated that among general health variables, anxiety and depression are predictors of procrastination and totally 0.13 of variance can determine procrastination. Other findings showed that there is no meaningful difference between girl students in different academic majors on general health and procrastination. Current research findings are compatible with previous researches based on existence of positive relation between mental problems and procrastination.